HUMAN DIGNITY AND WOMEN’S RIGHTS IN SURROGACY: A Comparative Analysis of Islamic and International Human Rights Perspectives - Heidari, Fareshta (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2026)
This study explores surrogacy through the lenses of both international human rights and Islamic law, with particular attention to women’s reproductive rights, human dignity, and the well-being of children. As a modern reproductive practice, surrogacy raises complex ethical, legal, and religious questions. Although international human rights instruments do not explicitly regulate surrogacy, they emphasize principles such as autonomy, privacy, and gender equality, which support women’s freedom in reproductive decision-making. Islamic law, by contrast, approaches the issue differently within its two main traditions: Sunni and Shia. Sunni scholars generally prohibit surrogacy to safeguard lineage, preserve family integrity, and prevent the exploitation of women, while Shia scholars permit it under carefully defined conditions. Despite these distinctions, both frameworks share a common concern for protecting women’s dignity and preventing abuse. By examining the intersections and divergences between them, this study aims to illuminate the ethical, legal, and cultural complexities surrounding surrogacy, particularly in societies where religious and international legal systems coexist. This study argues that although both Islamic law and international human rights invoke human dignity in regulating surrogacy, neither framework fully resolves the tension between women’s reproductive autonomy and structural vulnerability, resulting in persistent risks of exploitation. However, farming human dignity either primarily as reproductive autonomy or as moral containment fails to fully address the structural inequalities that shape women’s participation in surrogacy arrangements.